Mineral nutrition for Cannabis sativa in the vegetative stage using response surface analysis - Kpai, Patrick Yawo; Adaramola, Oluwafemi; Addo, Philip Wiredu; MacPherson, Sarah; Lefsrud, Mark (Frontiers in Plant Science, 2024)
Cannabis cultivated for medical and adult use is a high-value horticultural crop in North America; however, we lack information on optimal mineral nutrition due to previous legal restrictions. This study evaluated the mineral requirements of nitrogen (N), phosphorus (P), and potassium (K) for cannabis in the vegetative stage using response surface analysis. Plants were cultivated in a hydroponic system with various nutrient solution treatments (mg L-1) of N (132.7, 160, 200, 240, 267.3), P (9.6, 30, 60, 90, 110.5), and K (20.8, 60, 117.5, 175, 214.2) according to a central composite design. Nutrient interactions (N x K; K x P; and N x P x K) had a significant effect on the vegetative growth of the cannabis plants. N x K interaction had a significant effect on leaf mass and stem mass. K x P interaction had a significant effect on dry root mass, leaf mass, stem mass, leaf area, specific leaf area, and chlorophyll a and b contents. N x P x K interaction had a significant effect on root mass, leaf mass, stem mass, stem diameter, leaf area, and chlorophyll a and b contents. The optimum concentrations of total nitrogen, P, K, calcium, and sulfur in the cannabis leaves were 0.54, 0.073, 0.27, 0.56, and 0.38 mg g-1, respectively. An increase in P and K concentration decreased the magnesium concentration in the leaves, but it was unaffected by the increase in N concentration. The recommended primary macronutrients for cannabis plants in the vegetative stage based on the maximum desirability and nutrient use efficiencies were 160 – 200 mg L-1 N, 30 mg L-1 P, and 60 mg L-1 K. These findings can offer valuable insight and guidance to growers regarding mineral requirements for cannabis during the vegetative stage.